Lumbar Hyperlordosis - Barbosa, Jorge; Interno de Medicina Física e de Reabilitação do Hospital de Curry Cabral (2013)
Objectives: To review the literature on lumbar hyperlordosis with a focus on developing a definition, addressingthe etiopathogenesis, the diagnosis and enunciating an etiologic classification. For each form, particularities,pathophysiology, clinics and treatment are described, within a rehabilitation framework.Material and Methods: Physical Medicine and Rehabilitation (PMR) reference textbooks and electronic databaseswere searched, using the terms “lumbar hyperlordosis”, “hyperlordosis”, “lumbar lordosis” and “lordosis”. Thesearch was limited to review articles published in English or French, in which the term was included in the title,abstract and/or the keywords and in which the abstract and the full article were available. After the selection ofinformation, support literature consisted in 4 chapters of textbooks and 40 scientific articles.Results: Lumbar lordosis is a curve on the sagittal plane of the lumbar spine with an anterior apex and can bemeasured in lateral view radiograph using Cobb’s method. The Scoliosis Research Society (SRS) stipulated asphysiological angles the range between 31º and 79º.The diagnosis of lumbar hyperlordosis is established when a curve with an angle greater than the physiologicalis identified. This pathology is frequently asymptomatic, although it can be manifested as low back pain andreduction of the flexibility of the lumbar spine. Lumbar hyperlordosis, according to SRS, can be classified aspostural (the most frequent form), congenital (due to anomalies of the vertebral embryonic development), postlaminectomy(iatrogenic), neuromuscular (resulting from muscle tone and strength imbalances), secondary to hipflexion contracture and associated with other causes. The forms associated with spondylolysis (common inadolescents that practice sports with repetitive lumbar hyperextension) and spondylolisthesis (attributed tomultiple etiologies) were included in the classification by several authors.The management of PMR in the treatment of lumbar hyperlordosis can involve general measures, kinesiotherapyand the use of braces; some cases have surgical indication.Conclusions: Lumbar hyperlordosis is a spine static change of simple diagnosis, based on a physical exam andradiological confirmation. PMR intervention has a major role in detecting this pathology and enhancing itstherapeutic options, thereby improving patients’ quality of life.Keywords: Lordosis; Lumbar Vertebrae; Rehabilitation.